2021
DOI: 10.1177/0021998320984247
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compressive response of 3D GFRP composites with shear thickening fluid (STF) matrix as cushioning materials

Abstract: Whereas most previous studies have focused on improving the penetration resistance of Shear Thickening Fluids (STFs) treated composites, in this study, the dynamic compressive response of single and multi-ply 3 D E-Glass Fiber Reinforced Polymer (GFRP) composites with the STF matrix was investigated by using a drop-weight low-velocity impact test. The experimental results revealed the STF improved the compressive and cushioning performance of the composites such that with increasing its concentration, further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Plastic deformation modes are typically quite comparable to those produced by quasi-static loading for low velocity impacts. 28,29…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic deformation modes are typically quite comparable to those produced by quasi-static loading for low velocity impacts. 28,29…”
Section: Introductionmentioning
confidence: 99%
“…Plastic deformation modes are typically quite comparable to those produced by quasi-static loading for low velocity impacts. 28,29 For industrial necessities as assembly and to reduce the weight of the energy-absorbing components, it is advised to provide cutouts like holes in the body of the structure. Cutouts have a negative impact on the energy-absorbing members' ðEACÞ.…”
Section: Introductionmentioning
confidence: 99%
“…Shear thickening fluid (STF) is a type of non-Newtonian fluid that exhibits a rapid and substantial augmentation in viscosity, often by several orders of magnitude, in response to escalating shear rates. [1][2][3][4][5][6] The behavior of STF resembles that of a solid-like material when subjected to applied stress due to the elevation in viscosity. Subsequent to the cessation of external loading, the STF reverts to its initial liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4]. To improve the dynamic performance of a GFRP under impact loading, studies have developed GFRP impregnated with shear-thickening fluid (GFRP-STF) composite materials and their mechanical properties have been examined under high-and low-velocity impacts [5][6][7][8][9][10][11][12]. Nevertheless, under extreme impact loads caused by explosions, vehicular and ship collisions, rockfall impacts, and other reasons, the ultimate failure strength and energy absorption capacity of a GFRP-STF composite may vary considerably owing to the strain-rate effect.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the ballistic tests showed that the STF effectively reduced the penetration depth of the GFRP, whereas the rheological performance of the STF had a considerable impact on the ballistic performance. Regarding the compression responses of GFRP-STF composites, Jeddi and Yazdani [7] found that a STF improves the compression properties of a GFRP, which are enhanced with the increase in the STF concentration and the modification of the rheological properties. On this basis, Jeddi and Yazdani [8] reported that the STF concentration also had a considerable effect on the puncture resistance of the GFRP-STF fiber fabric.…”
Section: Introductionmentioning
confidence: 99%